1992
DOI: 10.1107/s0108768192002465
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of RbTiOAsO4, KTiO(P0.58,As0.42)O4, RbTiOPO4 and (Rb0.465,K0.535)TiOPO4, and analysis of pseudosymmetry in crystals of the KTiOPO4 family

Abstract: The crystal structures of RbTiOAsO4, KTiO(Po.58,-AS0.42)O4, RbTiOPO4 and (Rbo.465,Ko.535)TiOPO4, all of which are orthorhombic (space group Pna2~)and isostructural with KTiOPO4, have been determined from single-crystal X-ray diffraction data and refined to R factors between 0.027 and 0.040. The results are used for an analysis of structural trends in crystals of the KTiOPO4 family by comparison of the room-temperature structures with that proposed for the high-temperature prototypic phase (space group Pnan). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 6 publications
(7 reference statements)
6
78
0
Order By: Relevance
“…The distribution of Rb and Cs over the M(1) and M(2) sites shows that Cs atoms have a clear preference for the larger M(2) site, which is consistent with previous studies of mixed cation isomorphs (Thomas et al, 1994;Thomas et al, 1992;Northrup et al, 1994). Furthermore, the M(1) and M(2) cages increase in size as more Cs is incorporated.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The distribution of Rb and Cs over the M(1) and M(2) sites shows that Cs atoms have a clear preference for the larger M(2) site, which is consistent with previous studies of mixed cation isomorphs (Thomas et al, 1994;Thomas et al, 1992;Northrup et al, 1994). Furthermore, the M(1) and M(2) cages increase in size as more Cs is incorporated.…”
Section: Discussionsupporting
confidence: 79%
“…Pisarev et al (1990) showed for TlTiOPO 4 (TTP) that the phase transition was characterized by a soft mode associated with displacements of Tl along c coupled with the TiO 6 vibrational modes. This has focused considerable attention upon the role of the monovalent cations in the structural phase transition and, in general, the heavier the cation in a particular framework, the smaller its displacement from the highsymmetry position and the lower T c (Thomas et al, 1992). From the static picture of displacements revealed by the room-temperature structure determinations, a linear relationship for the phase transition temperature T c has been found: T c = GÁD 2 + C, where ÁD 2 is the square of the shift of the M cation relative to the TiO 6 /AsO 4 framework and G and C take the values 840 (96) K A Ê À2 and 988 (21) K, respectively .…”
Section: Pseudo-symmetrymentioning
confidence: 99%
“…No papers in the literature seem to deal with this subject for the CI-Br couple. We have only found some reports about cationic substitution (Nord, 1983;Thomas, Mayo & Watts, 1992 (1996). C52, 812-817 Trimethyloxosulfonium Salts.…”
Section: Commentmentioning
confidence: 99%
“…It crystallizes in the orthorhombic space group [1]. Because of its non-linear optical properties, RTP can be used for frequency doubling the light emitted by Yb and Nd lasers with a wavelength close to 1 m [2].…”
Section: Introductionmentioning
confidence: 99%